Exploring barriers to the integration of digital tools in teaching and learning in rural high schools: A South African case study - Sakyiwaa Boateng; Nomandla Bloko (Universitas Majalengka, 2026)
The integration of digital tools in education has become an essential component of 21st-century teaching and learning. However, in South Africa’s rural contexts, particularly in the Alfred Nzo West District of the Eastern Cape, the adoption of digital technologies remains limited and uneven. Purpose: This study examines the barriers to teaching and learning with digital tools in rural high schools, with a specific focus on infrastructural, pedagogical, and socio-economic challenges that hinder effective technology integration. Methods: This study employs a qualitative research approach to investigate the challenges teachers and learners face in schools when using digital tools for teaching and learning. Data were collected through semi-structured interviews, classroom observations, and document analysis in selected high schools in the district. The data was analysed thematically. Results: The findings indicate that inadequate infrastructure, unreliable internet connectivity, lack of digital devices, insufficient teacher training, and limited support from education authorities all constrain the effective use of digital tools in schools. In addition, socio-economic inequalities and language barriers exacerbate the digital divide, restricting equitable access to technology-enhanced learning. Despite these constraints, the study identifies instances of innovation and resilience among teachers who creatively use the limited resources available to facilitate digital learning. Implications: The study argues that for digital education to become sustainable in rural schools, targeted policy interventions, adequate funding, continuous professional development, and strong community partnerships are required to bridge the digital divide. This study contributes to the growing body of literature on digital learning in developing contexts by highlighting the specific barriers encountered in South African rural schools and proposing context-sensitive strategies for improvement.